IT COST OPTIMIZATION CASE STUDY: WIFI SERVICE AT SOEKARNO-HATTA INTâL AIRPORT - Suharyana
PT Angkasa Pura II (Persero), herein after refer to as “Angkasa Pura II”, is a State-Owned Enterprise engaged in the airport services and airport related services in Indonesia. As part of its mission to give a trusted, consistent, and pleasure travel experience to customer, Angkasa Pura II provides a free WiFi service at airports under its management, including at Soekarno-Hatta International Airport. Previously, the free WiFi service was provided through “commercial approach”, where a third party provided the WiFi service for free to Angkasa Pura II and they were given an exlusive rights to commercialize the advertisement slot at the captive portal in return. But the approach did not work as expected. As the impact, it resulted in poor WiFi service that in the end ultimately damaging the quality of service in Soekarno-Hatta International Airport as a whole. To fix the problem, Angkasa Pura II launch a new program to revitalize the free WiFi service quality using a different approach: the service approach. Angkasa Pura II took over the costs needed to provide a good free WiFi service as a pure service to improve customer satisfaction. The budget has been confirmed, Angkasa Pura II is now ready to spend about Rp 25 billions rupiah per year, and this number can continue to increase if it is not managed properly.